2013
DOI: 10.4161/auto.23877
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and formation of tubulovesicular autophagosomes provide a barrier against nonviral gene delivery

Abstract: Cationic liposome (lipoplex) and polymer (polyplex)-based vectors have been developed for nonviral gene delivery. These vectors bind DNA and enter cells via endosomes, but intracellular transfer of DNA to the nucleus is inefficient. Here we show that lipoplex and polyplex vectors enter cells in endosomes, activate autophagy and generate tubulovesicular autophagosomes. Activation of autophagy was dependent on ATG5, resulting in lipidation of LC3, but did not require the PtdIns 3-kinase activity of PIK3C3/VPS34.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 23 publications
3
75
1
Order By: Relevance
“…Recently, it was shown for the first time that autophagy is a potential barrier in non-viral gene delivery after transfection of cells with nanoparticles. With electroporation, however, an autophagy response was not noted (17). Also previously, we suggested that autophagy could be responsible for the long term endosomal entrapment of nanoparticles in Retinal Pigment Epithelial (RPE) cells (18).…”
Section: Introductionmentioning
confidence: 94%
“…Recently, it was shown for the first time that autophagy is a potential barrier in non-viral gene delivery after transfection of cells with nanoparticles. With electroporation, however, an autophagy response was not noted (17). Also previously, we suggested that autophagy could be responsible for the long term endosomal entrapment of nanoparticles in Retinal Pigment Epithelial (RPE) cells (18).…”
Section: Introductionmentioning
confidence: 94%
“…In addition, evidence for the fusion between autophagosomes and damaged lysosomes that expose glycans had not been found (11), but amphisome formation cannot be excluded in the CPP treatment condition even though CPP-induced double-membraned autophagosomes seem to contain membranous materials, which could be the damaged endosomes (4,6). Similarly, amphisome formation cannot be excluded during the formation of LC3-TVS induced by cationic liposomes (31). Future studies should be directed to address this critical issue in the treatment with CPPs and cationic lipid agents.…”
Section: Cpp Treatment Causes Endosome Damage-here We Havementioning
confidence: 99%
“…Notably, inhibition of either autophagy initiation or lysosome degradation could significantly increase the expression of DNA transfected with CPPs (38) or with cationic lipids (31). Thus, autophagy can serve as a defense mechanism against foreign DNA entering via the endosome system.…”
Section: Cpp Treatment Causes Endosome Damage-here We Havementioning
confidence: 99%
See 1 more Smart Citation
“…However, the molar ratio of DOTAP/chol has an impact on the transfection efficiency. Previous research has indicated that DOTAP/chol liposomes with a molar ratio of 1:1 or 2:1 had a high transfection efficiency (3,5). To achieve a higher transfection efficiency, on the one hand, it is necessary to identify the optimal molar ratio of DOTAP/chol for use in the preparation of liposomes.…”
Section: Introductionmentioning
confidence: 99%